Olive mill wastewater treatment using vertical flow constructed wetlands (VFCWs) - Muna Abu-Dalo; Duaa Abu-Dalo; Maha Halalsheh; Abeer Al Bawab (BMC Chemistry, 2024)
Abstract The study explores a synergistic two-phase system to treat olive mill wastewater (OMW), comprising a multilayer adsorbent filter (pretreatment) and a vertical flow constructed wetland (VFCW). The pretreatment phase includes layers of commercial granular activated carbon (CGAC) and volcanic tuff (VT), while the VFCW phase consists of planted tank with Phragmites australis reeds and unplanted tanks. Initially, municipal wastewater is introduced into the VFCW to establish the required microbial community. Then, pre-treated OMW is passed through the VFCW. The removal rates of various pollutants were assessed. The planted VFCW showed superior removal efficiencies, averaging 97.82% for total chemical oxygen demand (CODT), 92.78% for dissolved oxygen demand (CODd), 99.61% for total phenolic compounds (TPC), 98.94% for total nitrogen (TN), 96.96% for ammonium, and 95.83% for nitrate. In contrast, the unplanted VFCW displayed lower removal efficiencies, averaging 91.47% for CODT, 77.82% for CODd, 98.53% for TPC, 97.51% for TN, 92.04% for ammonium, and 90.82% for nitrate. These findings highlight the significant potential of VFCWs, which offer an integrated approach to OMW treatment by incorporating physical, chemical, and biological mechanisms within a single treatment system. Graphical Abstract